Globalization and local profiles of economic growth and industrial change - Wolfgang Dauth; Jens Suedekum (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
We analyze how globalization has affected the sectoral anatomy of regional growth in Germany over the period 1978-2008. The aggregate German economy is characterized by a secular decline of manufacturing and a rise of modern service industries. This trend - also known as Petty's law - is not uniform across space, however. Some regions exhibit it at an even accelerated pace, while other regions have reinforced their manufacturing specializations. We first categorize all German regions into one of three groups, with protrend, anti-trend or featureless growth. Afterwards we propose an explanation why a particular region ended up in one of those groups: We argue that the regional profiles of growth and change are systematically related to the initial sizes, and the import and export exposures of the local manufacturing sectors.
Keywords: R11; O14; F16; 330; structural change; local industry compositions; trade exposure; local employment growth